Liver X Receptor Activation Impairs Neutrophil Functions and Aggravates Sepsis. (29th November 2019) - Souto, Fabrício O; Castanheira, Fernanda V S; Trevelin, Silvia C; Lima, Braulio H F; Cebinelli, Guilherme Cesar Martelossi; Turato, Walter M; Auxiliadora-Martins, Maria; Basile-Filho, Anibal; Alves-Filho, Jose Carlos; Cunha, Fernando Q
Abstract: Background: Liver X receptors (LXRs) are nuclear receptors activated by oxidized lipids and were previously implicated in several metabolic development and inflammatory disorders. Although neutrophils express both LXR-α and LXR-β, the consequences of their activation, particularly during sepsis, remain unknown. Methods: We used the model of cecal ligation and puncture (CLP) to investigate the role of LXR activation during sepsis. Results: In this study, we verified that LXR activation reduces neutrophil chemotactic and killing abilities in vitro. Mice treated with LXR agonists showed higher sepsis-induced mortality, which could be associated with reduced neutrophil infiltration at the infectious foci, increased bacteremia, systemic inflammatory response, and multiorgan failure. In contrast, septic mice treated with LXR antagonist showed increased number of neutrophils in the peritoneal cavity, reduced bacterial load, and multiorgan dysfunction. More important, neutrophils from septic patients showed increased ABCA1 messenger ribonucleic acid levels (a marker of LXR activation) and impaired chemotactic response toward CXCL8 compared with cells from healthy individuals. Conclusions: Therefore, our findings suggest that LXR activation impairs neutrophil functions, which might contribute to poor sepsis outcome.